Coagulation dysfunction is associated with severity of COVID‐19: A meta‐analysis. Issue 2 (14th October 2020) - Zhu, Jieyun; Pang, Jielong; Ji, Pan; Zhong, Zhimei; Li, Hongyuan; Li, Bocheng; Zhang, Jianfeng; Lu, Junyu
Abstract: To systematically analyze the blood coagulation features of coronavirus disease 2019 (COVID‐19) patients to provide a reference for clinical practice. An electronic search in PubMed, EMbase, Web of Science, Scopus, CNKI, WanFang Data, and VIP databases to identify studies describing the blood coagulation features of COVID‐19 patients from 1 January 2020 to 21 April 2020. Three reviewers independently screened literature, extracted data, and assessed the risk of bias of included studies, then, the meta‐analysis was performed by using Stata 12.0 software. Thirty‐four studies involving 6492 COVID‐19 patients were included. Meta‐analysis showed that patients with severe disease showed significantly lower platelet count (weighted mean differences [WMD]: −16.29 × 10 9 /L; 95% confidence interval [CI]: −25.34 to −7.23) and shorter activated partial thromboplastin time (WMD: −0.81 seconds; 95% CI: −1.94 to 0.33) but higher D‐dimer levels (WMD: 0.44 μg/mL; 95% CI: 0.29‐0.58), higher fibrinogen levels (WMD: 0.51 g/L; 95% CI: 0.33‐0.69) and longer prothrombin time (PT; WMD: 0.65 seconds; 95% CI: 0.44‐0.86). Patients who died showed significantly higher D‐dimer levels (WMD: 6.58 μg/mL; 95% CI: 3.59‐9.57), longer PT (WMD: 1.27 seconds; 95% CI: 0.49‐2.06) and lower platelet count (WMD: −39.73 × 10 9 /L; 95% CI: −61.99 to −17.45) than patients who survived. Coagulation dysfunction is common in severe COVID‐19 patients and it is associated with severity of COVID‐19. Highlights: 1. Covid‐19 is a new respiratory disease and it has spread rapidly around the world. 2. Coagulation dysfunction is associated with severity of COVID‐19. 3. Monitoring blood coagulation parameters during course of the disease may be helpful for the early identification of severe COVID‐19 patients.